Visit‐to‐visit variability of clinical risk markers in relation to long‐term complications in type 1 diabetes. Issue 5 (23rd November 2020) - Rotbain Curovic, Viktor; Theilade, Simone; Winther, Signe Abitz; Tofte, Nete; Tarnow, Lise; Jorsal, Anders; Parving, Hans‐Henrik; Persson, Frederik; Hansen, Tine Willum; Rossing, Peter
Abstract: Background: Clinical characteristics such as HbA1c, systolic blood pressure (SBP), albuminuria and estimated glomerular filtration rate (eGFR) are important when treating type 1 diabetes. We investigated the variability in these measures as risk markers for micro‐ and macrovascular complications. Methods: This prospective study included 1062 individuals with type 1 diabetes. Visit‐to‐visit variability of HbA1c, SBP, albuminuria and eGFR was calculated as the SD of the residuals in individual linear regression models using all available measures in a specified period of 3 years (VV). Endpoints included were as follows: cardiovascular events (CVE) defined as myocardial infarction, non‐fatal stroke, or coronary or peripheral arterial intervention; end‐stage kidney disease (ESKD) defined as eGFR <15 ml/min/1.73 m 2, chronic dialysis or kidney transplantation; eGFR decline ≥30%; and mortality. Adjustment included age, sex, cholesterol, HbA1c, SBP, body mass index, smoking, albuminuria, eGFR, and mean, intercept, slope of respective exposure variables and regression models. Results: SBP VV was significantly associated with CVE (adjusted hazard ratio per 50% increase, (CI 95%); p: 1.21 [1.05–1.39]; p = 0.008), ESKD (1.51 [1.16–1.96]; p = 0.002) and mortality (1.25 [1.09–1.44]; p = 0.002). HbA1c VV was significantly associated with mortality (1.51 [1.30–1.75]; p < 0.001); albuminuria VV with eGFR decline (1.14 [1.08–1.20]; p = 0.024) and ESKD (1.14 [1.02–1.27]; p < 0.001), but neither CVE nor mortality. Adjusted eGFR VV was not associated with endpoints. Conclusion: In type 1 diabetes, higher variability of basic clinical risk markers adds important risk stratification information for the development of micro‐ and macrovascular complications. Abstract : Click here to access the podcast for this paper